Gender Differences in High-Stakes Performance and College Admission Policies - Andreu Arenas; Caterina Calsamiglia (Institute of Labor Economics (IZA), 2022)
We investigate the effect of increasing the weight of standardized high-stakes exams at the expense of high school grades for college admissions. Studying a policy change in Spain, we find a negative effect of the reform on female college admission scores, driven by students expected to be at the top. The effect on admission scores does not affect enrolment, but the percentage of female students in the most selective degrees declines, along with their career prospects. Using data on college performance of pre-reform cohorts, we find that female students most likely to lose from the reform tend to do better in college than male students expected to benefit from the reform. The results show that rewarding high-stakes performance in selection processes may come along with gender differences unrelated to the determinants of subsequent performance.
Keywords: J16; I23; I24; 330; college admissions; high-stakes exams; gender gaps